Suspension oxidative roasting for enhanced gold leaching from a quartz-rich refractory gold ore: Process optimization and microstructural evolution - Yan Song; Jianping Jin; Yanjun Li; Bing Zhao; Min Sun; Yuexin Han (Minerals Engineering, 2026)

Enhanced peroxymonosulfate activation for antibiotic removal using Ni1Mn1Fe1-LDO/g-C3N4: Metallic electronic synergy and oxygen vacancy effects - Wenqi Bu; Zhan Wang; Tao Zhu; Zhaocai Wu; Siqi Liu; Jiang Li; Qianwen Wang; Shuaishuai Xin; Xiaozhe Song; Yanjun Xin; Qinghua Yan; Guocheng Liu (Environmental Research, 2026)

Unveiling TWC replacement benefits in in-use vehicles from a concentration-reactivity-toxicity perspective - Jie Yao; Xinping Yang; Yongdong Wang; Jian Wang; Yanjun Wang; Chao Peng; Hongfei Chen; Xin Li; Yunjing Wang; Yan Ding (Environmental Pollution, 2026)

Developing Si/Al-rich biochar for higher incorporation in building materials: Enhanced mechanics and reduced carbon emissions - Gang Huang; Lei Wang; Liang Chen; Yanjun Hu; Kitae Baek; Shurong Wang; Jianhua Yan (Sustainable Chemistry and Pharmacy, 2026)

New insights into the temporal speciation of phosphorus during anaerobic digestion of wetland biomass wastes - Fan Yu; Junxia Wang; Zhi Wang; Lan Mu; Xutong Wang; Qianqian Guo; Xiaoqiang Cui; Yanjun Hu; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Progressive Failure Mechanism and Prediction Model of Geogrid‑Reinforced Embankments under Long‑Term Service Conditions in Xinjiang, China - Weijia Sun; Caijin Wang; Xuejun Liu; Liangfu Xie; Yanjun Li; Yan Wang; Yuelong Ha; Chuanhong Qiang; Weilin Ma; Annan Zhou; Songyu Liu (Transportation Geotechnics, 2026)

Quality deterioration and its molecular basis in postharvest Flammulina filiformis: Insights from physiological and transcriptomic profiling under simulated storage environments - Yan Wang; Chong Shi; Yanjun Duan; Haikuo Cui; Jianxing Zhai; Zilong Deng; Benard Muinde Kimatu; Donglu Fang (Postharvest Biology and Technology, 2026)

Adaptive mode and controller switching for intelligent motion control of robotic fish with hybrid propulsion system - Fagang Bai; Xianglei Yan; Lei Guo; Yanjun Liu; Xin Pan; Gang Xue (Ocean Engineering, 2026)

Using a moderately complex model to quantify the contributions of increased precipitation, reduced pumping, and water diversion to groundwater recovery in the southern Hebei Plain - Xia Liu; Zhe Wang; Leilei Min; Yucui Zhang; Yanjun Shen; Yan-Jun Shen (Journal of Cleaner Production, 2026)

High internal phase Pickering emulsions stabilized by submicron composite particles via ultrasound-assisted binding of lysine to whey protein isolate: Interfacial behavior, microstructural evolution and stabilization enhancement - Yanjun Li; Yingying Sui; Luodi Xu; Olayemi Eyituoyo Dudu; Xuenan Gao; Yan Li; Jinju Cheng; Xiaodong Li (Food Chemistry, 2026)

Geochemical and hydrological controls on aragonite versus calcite precipitation in speleothems and paleoclimatic implications - Rui Zhang; Haiwei Zhang; Christoph Spötl; Carlos Pérez-Mejías; Zixin Guan; Heather Stoll; Yanjun Cai; Liangcheng Tan; Fudong Wang; Xunlin Yang; Yan Yang; Lijuan Sha; et al. (Chemical Geology, 2026)

A multi-pronged strategy towards one-stage partial nitritation/anammox in a lab-scale MABR - Yimeng Li; Dongdong Xu; Yan Lu; Chenkai Niu; Yanjun Shao; Jianhua Guo (Water Research, 2026)

Semi-industrial-scale detoxification of cyanide tailings by suspension oxidation roasting and feasibility evaluation for underground backfilling - Bing Zhao; Yan Song; Shuai Yuan; Peng Gao; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Data-driven insights into real-world N2O emissions across conventional and hybrid vehicles: Transient impacts and driving factor identification - Huayang Zhao; Mingshen Ma; Zhou Yin; Han Jiang; Haiguang Zhao; Lei Zu; Yitu Lai; Yunjing Wang; Yanjun Wang; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Magnetic droplet carrier robot integrated with AI-fueled on-site detection - Long Jiao; Wentao Yan; Yanjun Hu; Dongliang Li; Zhenting Xie; Zibing Pan; Qianqian Guo; Xiao Yan; Xiang Wu; Qi Wu (Chemical Engineering Journal, 2026)

A synergistic metal ion–silane strategy enables fire-safe, water-repellent, and mold-resistant flattened bamboo board - Longchao Ma; Genmiao Wan; Yan Wang; Chenkai Dou; Danhe Liu; Yue Jiao; Hao Sun; Xinzhou Wang; Yi Chen; Qiliang Fu; Yanjun Li (Chemical Engineering Journal, 2026)

Revealing mitochondrial energy/redox imbalance with a dual-channel ATP/GSH probe under conditions of epileptiform activity - Pengan Wang; Huifeng Zhang; Yan Zhang; Yanjun Chen; Qiong Jia (Analytica Chimica Acta, 2026)

A high-strength interpenetrating-network cotton-derived biochar aerogel: Coupling uranium(VI) removal and interfacial solar desalination - Yang Wang; Yun Wang; Yang Li; Yanjun Du; Hao Jiang; Ruiyang Chang; Xingnong Wu; Yan Liu; Dingzhong Yuan; Xiaoyan Li (Process Safety and Environmental Protection, 2026)

Laboratory study on a new enhancing method for an in-service crushed-rock embankment underlain by permafrost - Yanbo Hao; Yuanhong Dong; Miaomiao Bai; Yanjun Ji; Jiafan Zhang; Huimei Zhang; Long Jin; Donggen Chen; Xusheng Wan; Zhongrui Yan; Jianguo Lu; Pan Chen (Cold Regions Science and Technology, 2026)

Potential mechanism of Lactiflorin in treating ulcerative colitis via modulation of the PI3K/AKT pathway: a study integrating network analysis, bioinformatics analysis, and experimental evidence - Mengjia Zhang; Haotian Li; Ningjuan Yan; Man Meng; Xiaolan Su; Yanjun Liu; Runhua Chen; Jianqin Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

High internal phase emulsions stabilized by milk protein-arabinoxylan-quercetin ternary complex: Enhanced environmental stability and fat digestive property (Milk protein-AX-Q complex-stabilized HIPEs: Stability and digestion) - Xuenan Gao; Peizhu Liu; Sirong Li; Olayemi Eyituoyo Dudu; Yanjun Li; Yan Li; Hongfang Yang; Jinju Cheng; Tingsheng Yan (Journal of Food Engineering, 2026)

Biochar reshapes phosphorus distribution in soil aggregates and improves rice phosphorus uptake - Jiajun Wu; Bin Zhou; Zhehao Huang; Zichuan Li; Jingyuan Pan; Kaihao Zhang; Cheng Liu; Yanjun Chai; Yan Li; Muhammad Azeem; Nicholas Clarke; Shengdao Shan (Soil Ecology Letters, 2026)

Coral-based reconstruction of interannual and decadal SST variability in the northern South China Sea during the mid-Holocene - Zhiheng Wu; Tingli Yan; Rui Tang; Ben Wang; Yanjun Mei; Ning Zhao (Geo-Marine Letters, 2026)

Simultaneous cyanide detoxification and sulfur immobilization in low-sulfur cyanide tailings via sustainable oxidation roasting: process optimization and mechanistic insights - Bing Zhao; Yan Song; Shuai Yuan; Peng Gao; Yuexin Han; Yanjun Li (Waste Management, 2026)

Study on antiviral drugs degradation by UV/NH2Cl: Combination of experiments and quantum chemical calculation - Zongyu Yan; Mian Wu; Haoran Wang; Tong Xu; Shuaishuai Xin; Qianwen Wang; Guocheng Liu; Qinghua Yan; Yanlong Sun; Chengzhi Zhou; Ya-nan Zhang; Yanjun Xin (Journal of Environmental Chemical Engineering, 2026)

Electro-trapping uranium(VI) by ternary phosphate-functionalized polymer / molybdenum disulfide / pod shell-derived biochar composite electrode - Dongqing Huang; Yun Wang; Yang Wang; Qidong Ye; Yang Li; Hao Jiang; Yanjun Du; Yan Liu; Dingzhong Yuan; Xianping Luo (Journal of Environmental Management, 2026)

Occurrence and distribution of phthalate esters in stormwater runoff and coastal water receiving bodies, Macao, South China - Yutang Luo; Tianyi Zhang; Yaru Cao; Qiying Jian; Aolei Du; Jun Yan; Yanjun Li; Youxiang Xu; Guoyuan Zhu; Xiong Xiong; Chenxi Wu; Kai Zhang (Environmental Pollution, 2026)

Metabolomic profiling reveals activity-correlated chemotypes and strain-specific metabolites in mangrove-derived actinomycetes - Bonan Yan; Ming Chen; Ling Li; Peixi Zhang; Ki Shi; Li Guo; Yixin Tang; Chunlan Li; Yanjun Di; Chen Zhu; Yuting Wu; Chenlei Lian; et al. (Natural Product Research, 2026)

Rainfall partitioning and interception simulation for typical species in the Taihang Mountains, China - Bo Guo; Hui Yang; Chunyu Zhu; Zhibang Yan; Jiansheng Cao; Yanjun Shen (Agricultural and Forest Meteorology, 2026)

NADbP: A morphological method to characterize the coupling between landslide evolution and river profile disequilibrium - Ruixin Long; Xiaoyan Zhao; Yanjun Yan; Junhong Hu; Liming Jian (Engineering Geology, 2026)

Microwave assisted alkali activated porous carbon from phenolic resin waste for high capacity methylene blue removal - Yanjun Yin; Mengjie Bai; Wenxu Wang; Xiaotian Zhao; Weide Yuan; Yongwei Li; Yuying Yan; Yujie Feng; Wenjie Zhu; Xinyu Wang; Zhihao Fang; Wei Zhang (Environmental Geochemistry and Health, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Elucidating microplastic adsorption mechanisms in biomass composite materials through interpretable machine learning - Huiling Li; Yimin Shi; Junhao Liu; Zhichen Ba; Shengkai Liu; Birong Yan; Daxin Liang; Yanjun Xie (Journal of Hazardous Materials, 2026)

Biochar promoted soil organic carbon accumulation and aggregate stability by increasing the content of organic complex metal oxides in paddy soil - Jiajun Wu; Bin Zhou; Zichuan Li; Cheng Liu; Yan Li; Yulin Wang; Ning Zhao; Zhuozhe Wang; Yanjun Chai; Antonio Scopa; Marios Drosos; Vishnu D. Rajput; et al. (Soil and Tillage Research, 2025)

Safe recycling of oxytetracycline fermentation residue by thermal pretreatment coupled with compost: Antibiotic degradation, resistance gene removal, nutrient release, and soil improvement - Guocheng Liu; Zhiying Li; Wenzhuo Xu; Lingyun Meng; Xicheng Yuan; Jinying Li; Xue Li; Qianwen Wang; Qinghua Yan; Shuaishuai Xin; Mengwei Xie; Yanling Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Activating graphitic carbon via a core/shell WO3/carbon architecture for electrocatalytic deactivation of dilute antibiotics - Wenyang Fu; Yanjun Yin; Jiahong Zou; Chunyang Dan; Shenbin Zheng; Huimin Sui; Yinan Liu; Yan Zou; Heng Shi; Guangming Jiang (Chemical Engineering Journal, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

CFD simulation of multifluid mixing and structure optimization of rotating liquid film reactor for magnesium hydroxide production - Wenwen Lin; Jiahao Wan; Yingying Zhang; Wenyan Liu; Kaitao Li; Xiongzhong Yan; Jicang Li; Shengting Li; Wendi Liu; Yanjun Lin (Chemical Engineering Journal, 2025)

In-situ pH regulation of biomass-based hydrogel composite: A green approach to efficient lithium ion capture from salt lake brine - Shengkai Liu; Chunling Cao; Huiling Li; Wenxuan Wang; Birong Yan; Junreng Liu; Wei Wang; Tai Peng; Daxin Liang; Yanjun Xie (Chemical Engineering Journal, 2025)

Reliable enrichment monitoring and removal of CrO42− and S2− using multivalent W-doped Ag quantum-dot biomimetic nanozyme - Ruhui Shang; Yanjun Han; Huitian Zhi; Xujie Wang; Yingchao Yang; Xiao Zhu; Lei Hu; Zhengquan Yan (Analytica Chimica Acta, 2025)

Trajectory tracking control of robotic fish in offshore disturbance environments via disturbance observer-based inverse sliding mode - Juntao Sun; Yanjun Liu; Fagang Bai; Xianglei Yan; Enzhi Quan; Gang Xue (Frontiers in Marine Science, 2025)
Considering the complex offshore environment, where small robotic fish are exposed to surface disturbances from wave forces, suspended particles, and model uncertainties, as well as deep-water disturbances from bottom currents, this paper proposes an inverse sliding mode control strategy based on a disturbance observer to enhance trajectory tracking robustness. The research focuses on a tail-fin-driven bionic robotic fish. Utilizing its kinematic and dynamic models, a virtual control law based on an agent dynamics model is proposed, with the tail fin integrated as a real control input. A nonlinear disturbance observer with controllable convergence characteristics is developed to estimate and compensate for disturbances, including wave forces and model uncertainties. Additionally, a velocity error correction function is introduced to mitigate the impact of strong disturbances. Based on Lyapunov theory, an adaptive sliding mode control law is derived to ensure system stability. The control law for the caudal fin swing angle and bias is obtained by inverting the virtual control inputs, applied to the robotic fish’s accurate model. Numerical simulations show that the disturbance observer’s tracking error remains below 5%, and the trajectory tracking error is within 0.1 meters, representing only 2.2% of the robotic fish’s body length. Compared to mainstream control methods, the proposed approach significantly enhances robustness in contrast to the conventional sliding mode control with observers, and exhibits substantially smaller tracking errors, especially during trajectory transitions.

Molecular fingerprints of dissolved organic matter leached from microplastics over prolonged photochemical aging: Implications for aquatic carbon cycling - Zekun Zhang; Zhao Liang Chen; Yanjun Liu; Yuanbi Yi; Ruanhong Cai; Ming Ye; Mengyang Liu; Meng Yan; Kenneth M.Y. Leung; Ding He (Water Research, 2025)

Short-term emissions effect of rainfall erosion on soil CO2 in red soil sloped farmland in southern China - Keyu Yan; Xiaohan Mei; Chuan Zhang; Yanmei Hu; Daoxiang Wang; Zhengfa Chen; Xiaofeng Yang; Yanrui Shao; Yanjun Mao (Soil and Tillage Research, 2025)

Multidimensional characterization of microplastic pollution in subtropical urban soils: Combining geospatial analysis and polymer risk indexing - Aolei Du; Yanjun Li; Qiying Jian; Kai Zhang; Yutang Luo; Jun Yan; Peixin Du; Deborah M. Power; Ying Li; Yibing Ma (Journal of Hazardous Materials, 2025)

Sunlight-driven hydrogen peroxide activation via copper hydroxyphosphate with broad spectrum response for imidacloprid degradation: Mechanism insight and DFT calculation - Haoran Zhang; Jiang Li; Yujiao Liu; Sihao Fu; Tianjie Su; Lingyu Meng; Yunfei Wang; Nian Ma; Guocheng Liu; Qinghua Yan; Yanjun Xin; Shuaishuai Xin (Chemical Engineering Journal, 2025)

Mechanistic insights into plasmon-mediated charge transfer in Pt@BiOBr/g-C3N4 S-scheme heterojunction for solar-driven water treatment - Jin Chen; Ke Li; Jie Yan; Suqing Qin; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Journal of Water Process Engineering, 2025)

Carbon footprint and environmental impact of reconstituted bamboo material based on life cycle assessment - Jingwen Chen; Yan Ma; Xiaomei Zhang; Nina Yan; Yanjun Li; Lei Xu; Zhichao Lou (Journal of Cleaner Production, 2025)

The gastrointestinal digestion fates and postprandial plasma fatty acid profiles of four dietary lipids with different unsaturated levels: A comparative study using Sprague-Dawley rats - Yanjun Guo; Zhan Ye; Yanjun Liu; Jiaying Yan; Rui Li; Yanan Wang; Yuanfa Liu (Food Bioscience, 2025)

Unlocking the potential of cotton-derived carbon aerogel for uranium extraction from real radioactive wastewater: A path to amidoxime and polyguanidine modification - Yang Wang; Yun Wang; Qi Ren; Zihao Feng; Yang Li; Yanjun Du; Xiaoyan Li; Yan Liu; Dingzhong Yuan; Tu Lan (Chemical Engineering Journal, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Chemical recycling of polyvinyl chloride: Recent progress in pretreatment dechlorination and chlorine recycling - Lidong Liu; Beibei Yan; Tiecheng Liu; Yanjun Zhang; Runping Du; Jinglan Wang; Guanyi Chen; Zhanjun Cheng (Resources, Conservation and Recycling, 2025)

Comparative in vivo study on the digestion behaviors of three typical saturated dietary fats in Sprague Dawley rats - Jiaying Yan; Yanjun Liu; Yanjun Guo; Rui Xu; Zhan Ye; Yuanfa Liu (Food Research International, 2025)

Inspiring the potential of graphene oxide aerogel for uranium(VI) electrosorption: A precursor reconfiguration strategy and synergistic integration with polyethyleneimine - Qi Ren; Yun Wang; Yang Wang; Zihao Feng; Yanjun Du; Changfu Wang; Yan Liu; Dingzhong Yuan; Hao Jiang; Yang Li (Desalination, 2025)

Enhanced PPP based on optimization of GNSS broadcast ionospheric model using robust and adaptive constraint - Xianggao Yan; Yanjun Du (Advances in Space Research, 2025)

Divergent Flowering Time Responses to Increasing Temperatures Are Associated With Transcriptome Plasticity and Epigenetic Modification Differences at FLC Promoter Region of Arabidopsis thaliana - Yu Han; Li Liu; Mengyu Lei; Wei Liu; Huan Si; Yan Ji; Qiao Du; Mingjia Zhu; Wenjia Zhang; Yifei Dai; Jianquan Liu; Yanjun Zan (Molecular Ecology, 2025)
Understanding the genetic, and transcriptomic changes that drive the phenotypic plasticity of fitness traits is a central question in evolutionary biology. In this study, we utilised 152 natural Swedish Arabidopsis thaliana accessions with re‐sequenced genomes, transcriptomes and methylomes and measured flowering times (FTs) under two temperature conditions (10°C and 16°C) to address this question. We revealed that the northern accessions exhibited advanced flowering in response to decreased temperature, whereas the southern accessions delayed their flowering, indicating a divergent flowering response. This contrast in flowering responses was associated with the isothermality of their native ranges, which potentially enables the northern accessions to complete their life cycle more rapidly in years with shorter growth seasons. At the transcriptome level, we observed extensive rewiring of gene co‐expression networks, with the expression of 25 core genes being associated with the mean FT and its plastic variation. Notably, variations in FLC expression sensitivity between northern and southern accessions were found to be associated with the divergence FT response. Further analysis suggests that FLC expression sensitivity is associated with differences in CG, CHG and CHH methylation at the promoter region. Overall, our study revealed the association between transcriptome plasticity and flowering time plasticity among different accessions, providing evidence for its relevance in ecological adaptation. These findings offer deeper insights into the genetics of rapid responses to environmental changes and ecological adaptation.

Simultaneously enhance nutrient removal and sludge settleability through hydrocyclone-based technology in a full-scale high-inert containing activated sludge process - Yanjun Shao; Sisi Chen; Xiang Tao; Weilan Yang; Tao Liu; Binzheng Wang; Yan Wang; Shuo Wang; Dongdong Xu; Jianhua Guo; Ji Li (Water Research, 2025)

Fabrication of TiO2/CuFeO2 composites for oxytetracycline degradation through heterogeneous photo-Fenton-like process under visible light - Xue Li; Jinying Li; Jiaying Song; Zhiying Li; Xicheng Yuan; Lingyun Meng; Wenzhuo Xu; Qianwen Wang; Qinghua Yan; Shuaishuai Xin; Chengzhi Zhou; Guocheng Liu; et al. (Journal of Environmental Management, 2025)

Resistivity and unfrozen water content of moraine soil at freezing temperatures: experiments and thermodynamic modeling - Xin Wei; Yanjun Shen; Zhenlei Wei; Yan Wang; Yongzhi Wang (Cold Regions Science and Technology, 2025)

Corrigendum to “Complete biosynthesis of the potential medicine icaritin by engineered Saccharomyces cerevisiae and Escherichia coli” [Sci. Bull. 66(18) (2021) 1906–1916] - Pingping Wang; Chaojing Li; Xiaodong Li; Wenjun Huang; Yan Wang; Jiali Wang; Yanjun Zhang; Xiaoman Yang; Xing Yan; Ying Wang; Zhihua Zhou (Science Bulletin, 2025)

Recent advances in heteroatom doping for performance optimization of inorganic metal-based lithium-ion adsorbents - Birong Yan; Shengkai Liu; Yimin Shi; Huiling Li; Xi Li; Yonggui Wang; Yabei Xu; Wei Wang; Tai Peng; Daxin Liang; Yanjun Xie (Desalination, 2025)

A new method for total organic carbon prediction of marine-continental transitional shale based on multivariate nonlinear regression - Xinyu Zhang; Yanjun Meng; Taotao Yan; Jinzhi Zhong; Zhen Qiu; Weibo Zhao; Liangliang Yin; Haojie Ma; Qin Zhang (Frontiers of Earth Science, 2025)

A wave-shaped CNN for marine-raft aquaculture-area extraction in SAR images - Guo Yanjun; Du Yunyan; Yan Ming; Xie Ting; Liu Moyun; Wang Nan (Computers and Electronics in Agriculture, 2025)

Visible-light-driven biochar supported CuMnO2 activating hydrogen peroxide for chlortetracycline degradation through promoting photocarriers separation - Shuaishuai Xin; Yiyun Wang; Haoran Zhang; Jiang Li; Zhihai Liu; Jing Jiao; Guocheng Liu; Chengzhi Zhou; Qinghua Yan; Yanjun Xin (Chemical Engineering Journal, 2025)

Insights into the enhanced removal of ciprofloxacin by Ni1Mn1Fe1-LDO activated peroxymonosulfate: Mechanism and application for antibiotic wastewater - Siqi Liu; Wenqi Bu; Xiangting Hou; Shixu Lu; Chengzhi Zhou; Xiaozhe Song; Qianwen Wang; Shuaishuai Xin; Guocheng Liu; Yanjun Xin; Qinghua Yan (Process Safety and Environmental Protection, 2025)

Impacts of street tree canopy coverage on pedestrians' dynamic thermal perception and walking willingness - Yijuan Sang; Yanjun Hu; Xiao Qin; Hai Yan; Renwu Wu; Fengtao Qian; Xinge Nan; Feng Shao; Zhiyi Bao (Sustainable Cities and Society, 2025)

Insights into relationship of oxidative potential of particles in the atmosphere and entering the human respiratory system with particle size, composition and source: A case study in a coastal area in Northern China - Ruiyu Li; Caiqing Yan; Yingze Tian; Yan Wu; Ruizhi Zhou; Qingpeng Meng; Li Fang; Yang Yue; Yanjun Yang; Haibiao Chen; Lingxiao Yang; Wei Jiang (Journal of Hazardous Materials, 2025)

Optimizing geographical traceability models of Chinese Lycium barbarum: Investigating effects of region, cultivar, and harvest year on nutrients, bioactives, elements and stable isotope composition - Yanjun Ju; Hejiang Liu; Shuhui Niu; Lu Kang; Lei Ma; An Li; Yan Zhao; Yuwei Yuan; Duoyong Zhao (Food Chemistry, 2025)

Long-term diversified cropping promotes wheat yield and sustainability across contrasting climates: Evidence from China and Switzerland - Zhengjun Yan; Yi Xu; Juncong Chu; Thomas Guillaume; Luca Bragazza; Hongjun Li; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Iron-doped titanium lithium-ion Sieves@Sodium alginate-enhanced carboxymethyl cellulose aerogels: A synergistic leap in adsorption and sustainability - Shengkai Liu; Birong Yan; Yu Han; Wei Wang; Yimin Shi; Yonggui Wang; Huiling Li; Junhao Liu; Zefang Xiao; Daxin Liang; Yanjun Xie (Journal of Cleaner Production, 2025)

Electrocatalytic conversion of nitrate to ammonia on the oxygen vacancy engineering of zinc oxide for nitrogen recovery from nitrate-polluted surface water - Wenyang Fu; Yanjun Yin; Shuxian He; Xiangyi Tang; Yinan Liu; Fei Shen; Yan Zou; Guangming Jiang (Environmental Research, 2025)

Biochar-supported MnFeO2 for heterogeneous photo-Fenton degradation of doxycycline: Collaborative promotion of electron transfer and H2O2 activation - Shuaishuai Xin; Yingchen Zhu; Yiyun Wang; Jiang Li; Haoran Zhang; Jing Jiao; Zhihai Liu; Qinghua Yan; Chengzhi Zhou; Guocheng Liu; Yanjun Xin (Chemical Engineering Journal, 2025)

L1-Tree: A novel algorithm for constructing 3D tree models and estimating branch architectural traits using terrestrial laser scanning data - Yuhao Feng; Yanjun Su; Jiatong Wang; Jiabo Yan; Xiaotian Qi; Eduardo Eiji Maeda; Matheus Henrique Nunes; Xiaoxia Zhao; Xiaoqiang Liu; Xiaoyong Wu; Chen Yang; Jiamin Pan; et al. (Remote Sensing of Environment, 2024)

The spatial scale and threshold effects of the relationship between landscape metrics and water quality in the Hutuo River Basin - Xia Liu; Yan-Jun Shen; Yuru Chang; Yanjun Shen (Journal of Environmental Management, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Cobalt single-site molecular Catalyst-mediated electrochemical Hydrodechlorination for detoxification of halogenated Antibiotics: Performance, reaction pathway and mechanism - Yinan Liu; Xiangyi Tang; Fei Shen; Jiahong Zou; Yanjun Yin; Zhaojie Jiao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Guangming Jiang; Hong Liu (Chemical Engineering Journal, 2024)

Photocatalytic activation of hydrogen peroxide via a novel CuFe2(PO4)2(OH)2 up-conversion material without rare-earth ions for doxycycline hydrochloride degradation - Yanan Dong; Jing Jiao; Zhihai Liu; Xu He; Panpan Wang; Qinghua Yan; Guocheng Liu; Chengzhi Zhou; Shuaishuai Xin; Yanjun Xin (Chemical Engineering Journal, 2024)

Assessing the spatial-temporal impacts of underlying surfaces on 3D thermal environment: A field study based on UAV vertical measurements - Fengtao Qian; Yanjun Hu; Renwu Wu; Hai Yan; Dingsheng Wang; Zhoubing Xiang; Kechun Zhao; Qian Han; Feng Shao; Zhiyi Bao (Building and Environment, 2024)

Selective depression of galena in the galena and chalcopyrite system by the Fe(II)-activated persulfate process - Qinbo Cao; Yan Yan; Heng Zou; Haiyu Zhang; Dianwen Liu; Shuming Wen; Yanjun Li (Minerals Engineering, 2024)

Evolution mechanism and treatment timing of penetrating fissures - Yanjun Zhang; Yueguan Yan; Yuanhao Zhu; Huayang Dai (Journal of Mountain Science, 2024)

Highly efficient and secure recycling of neomycin fermentation residue by optimum temperature: Nutrients release, neomycin degradation and safety evaluation - Yuefei Li; Jiaqi Hou; Dong Wang; Junhao Ma; Weikai Sun; Mingxiao Li; Zhihao Sun; Yulin Liu; Guocheng Liu; Qinghua Yan; Qianwen Wang; Beidou Xi; et al. (Chemical Engineering Journal, 2024)

Molecular characteristics and phylogenetic definition on the complete chloroplast genome of Petrocodon longitubus - Zaiqi Luo; FengXia Yan; Ronghui Jiang; Yanjun Chen; Changsha Luo; CongRui Li (Plant Biotechnology Reports, 2024)

Effects of GPS flex power on DCBs, ionospheric delays and positioning - Yanjun Du; Yuanxi Yang; Xiaolin Jia; Yan Xiang; Wanqiang Yao; Ting Ma; Qin Li (Advances in Space Research, 2024)

Generation and persistency of combustion-derived environmentally persistent free radicals from phenolic compounds over a Fe2O3/SiO2 surface - Yanjun Hu; Guohao Yang; Nan Zhou; Long Jiao; Lei Wang; Jianhua Yan (Chemosphere, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

A yarn-based sweat-activated battery constructed with conjugated electrospun nanofiber separators as a durable and high-capacity power source in textile electronics - Yanling Zheng; Huijun Sun; Yanjun Cheng; Wenhu Gao; Chenyu Wang; Jun Ju; Min Li; Xuemei Xiang; Wei Sun; Wei Wang; Zhisong Lu; Yan Qiao (Chemical Engineering Journal, 2024)

Which street is hotter? Street morphology may hold clues -thermal environment mapping based on street view imagery - Yanjun Hu; Fengtao Qian; Hai Yan; Ariane Middel; Renwu Wu; Minghui Zhu; Qian Han; Kechun Zhao; Han Wang; Feng Shao; Zhiyi Bao (Building and Environment, 2024)

SPR effect and internal electric field in Pt@BiOBr/(001)-TiO2 S-scheme heterojunction for visible-light-driven photocatalytic degradation of tetracycline hydrochloride and dyes - Jie Yan; Jin Chen; Xiaofeng Yang; Yueying Wang; Xinle Wang; Jianye Shi; Jing Zhang; Yuzhao Ma; Yanjun Li (Journal of Water Process Engineering, 2024)

Treatment of chromium-containing sludge using sintering and ironmaking combined technology: A risk-reducing strategy for environmental impact - Shengxuan Fan; Jinchao Wei; Xiaorong Xu; Ran Yan; Qian Li; Ying Liu; Yanjun Huang; Yi Wang; Guozhi Fan; Lei Zhang (Journal of Environmental Management, 2024)

Stat3 Has a Different Role in Axon Growth During Development Than It Does in Axon Regeneration After Injury - Qinwen Duan; Hongfei Zheng; Yanjun Qin; Jizhou Yan; Jian Wang; Shawn M. Burgess; Chunxin Fan (Molecular Neurobiology, 2024)

Upcycling MSWI fly ash into green binders via flue gas-enhanced wet carbonation - Miao Lu; Weizhe Ge; Yan Xia; Chen Sun; Xiaoqing Lin; Daniel C.W. Tsang; Tung-Chai Ling; Yanjun Hu; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

A real-time fluorogenic recombinase polymerase amplification microfluidic chip (on-chip RPA) for multiple detection of pathogenic microorganisms of penaeid shrimp - Qiang Li; Lijun Duan; Dongsheng Jin; Yuxin Chen; Yirong Lou; Qianjin Zhou; Zhongjie Xu; Fangjie Chen; Hongxian Chen; Guizong Xu; Maocang Yan; Guanjun Yang; et al. (Aquaculture, 2024)

Toxic effects and mechanisms of engineered nanoparticles and nanoplastics on lettuce (Lactuca sativa L.) - Yanjun Li; Xiaolong Lin; Guanghui Xu; Qiuliang Yan; Yong Yu (Science of The Total Environment, 2024)

Synergistic effects of ultrasonication on the flotation separation of galena from chalcopyrite using sulfuric acid as a depressant - Qinbo Cao; Yanjun Li; Heng Zou; Dianwen Liu; Yan Yan; Haiyu Zhang (Minerals Engineering, 2024)

Identifying hotspots of water table depth change by coupling trend with time stability analysis in the North China Plain - Xia Liu; Leilei Min; Yuru Chang; Yanjun Shen; Zhuoran Wang; Yan-Jun Shen (Science of The Total Environment, 2023)

Effects of gamma irradiation on the nutritional quality and physicochemical properties of Morchella angusticeps - Ailian Meng; Peng Gao; Pan Xu; Xin Jia; Jiang He; Yan Wang; Qian Chen; Yanjun Zhang; Yalu Qiu; Min Huang; Hao Chen (Food Bioscience, 2023)

Self-standing porous MXene film via in situ formed microgel induced by 2- methylimidazole for high rate supercapacitor - Sai Yan; Chenjing Shi; Zhen Tian; Dan Li; Yanjun Chen; Li Guo; Yanzhong Wang (Chemical Engineering Journal, 2023)

Tetraploid induction identification and transcriptome preliminary analysis of black currant (Ribes rubrum L.) - Ruiquan Dong; Yi Pei; Lingyan Hong; Jiangli Nie; Yuhang Chen; Huili Yan; Yanjun Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

A dual-enzyme microreactor based on encapsulation and covalent bond for enzymatic electrocatalytic CO2 reduction - Guanhua Liu; Lirong Wang; Lihang Yan; Hao Zhao; Yaoxuan Li; Liya Zhou; Ying He; Li Ma; Yunting Liu; Jing Gao; Yanjun Jiang (Chemical Engineering Journal, 2023)

Alternative scenarios for urban tree surveys: Investigating the species, structures, and diversities of street trees using street view imagery - Yanjun Hu; Han Wang; Hai Yan; Qian Han; Xinge Nan; Kechun Zhao; Zhiyi Bao (Science of The Total Environment, 2023)

Ammonia emission characteristics and ammonia injection control from stationary source in flue gas denitrification system - Zhiping Wang; Chengyi Sun; Aijun Shi; Jing Yan; Lei Nie; Lei Chen; Peili Zhou; Yanjun Ding; Yong Yang; Xianglong Jing (Journal of Cleaner Production, 2023)

High efficiency 2D/0D/3D Z-scheme rGO@g-C3N4/TiO2 nanobelt-tubes heterojunction for tetracycline degradation under visible light: Electrochemical synthesis, performance, and mechanisms - Xiaohan Ma; Guocheng Liu; Lu Wang; Shuaishuai Xin; Bin Zhang; Qinghua Chen; Qinghua Yan; Guangshan Zhang; Yingjie Zhang; Yanjun Xin (Journal of Environmental Chemical Engineering, 2023)

Field-grown cotton shows genotypic variation in agronomic and physiological responses to waterlogging - Yanjun Zhang; Yan Li; Tiantian Liang; Yabin Yuan; Zhenhuai Li; Shizhen Xu; Jianlong Dai; Shoujin Fan; Cundong Li; Hezhong Dong (Field Crops Research, 2023)

Flame retardant and multifunctional BC/MXene/MSiCnw/FRTPU aerogel composites with superior electromagnetic interference shielding via “Consolidating” method - Hengrui Wang; Kexin Chen; Yongqian Shi; Yanjun Zhu; Songqiong Jiang; Yan Liu; Shijie Wu; Chenxin Nie; Libi Fu; Yuezhan Feng; Pingan Song (Chemical Engineering Journal, 2023)

Highly efficient nanocomposite of Y2O3@biochar for oxytetracycline removal from solution: Adsorption characteristics and mechanisms - Jiaying Song; Lun Lu; Jian Wang; Xue Li; Jinying Li; Qianwen Wang; Haiyan Du; Shuaishuai Xin; Lina Xu; Qinghua Yan; Chengzhi Zhou; Guocheng Liu; et al. (Bioresource Technology, 2023)

Adsorption Characteristics and Mechanisms of Oxytetracycline on Nano Biochar: Effects of Environmental Conditions and Particle Aggregation - Wenqiang Jia; Xiangrui Pan; Jiaying Song; Jian Wang; Weikai Sun; Yanjun Xin; Qinghua Yan; Chengzhi Zhou; Hao Zheng; Guocheng Liu (Water, Air, & Soil Pollution, 2023)

Importation of a novel Indian Ocean lineage carrying E1-K211E and E2-V264A of Chikungunya Virus in Zhejiang Province, China, in 2019 - Lingxuan Su; Xiuyu Lou; Hao Yan; Zhangnv Yang; Haiyan Mao; Wenwu Yao; Yi Sun; Junhang Pan; Yanjun Zhang (Virus Genes, 2023)
The chikungunya virus (CHIKV) is widespread. In Zhejiang province, China, CHIKV infection is often associated with travelers from tropical and subtropical countries. In the present study, three CHIKV isolates from serum samples of travelers in Zhejiang province in 2019 were sequenced, and phylogenetically analyzed to study their molecular characteristics. Sequence analysis showed that the non-structural protein and the structural protein had 37 and 28 amino acid mutations, respectively; no mutation site was found at the E1-A226 residue, which could increase the adaptability of CHIKV to Aedes albopictus . All three samples carried two mutations, namely, E1-K211E and E2-V264A, which were introduced to Bangladesh around late 2015 and Thailand in early 2017. Phylogenetic analysis revealed that these three CHIKVs were Indian Ocean lineage of the East Africa/Central/South Africa genotype (ECSA) and that the MF773566 strain from Bangladesh (Australia/Bangladesh 2017) had the closest evolutionary relationship. The three CHICKs imported into Zhejiang province in 2019 belonged to the ECSA genotype and had multiple amino acid variation sites. The variation in the three samples provides a certain reference for the subsequent research on CHIKV evolution.

Fenton oxidation treatment of oxytetracycline fermentation residues: Harmless performance and bioresource properties - Wenqiang Jia; Jiaying Song; Jian Wang; Jinying Li; Xue Li; Qianwen Wang; Xiang Chen; Guocheng Liu; Qinghua Yan; Chengzhi Zhou; Shuaishuai Xin; Yanjun Xin (Chemosphere, 2023)

Evolution of the foreland basins on either side of the Tian Shan and implications for lithospheric architecture - Chao Li; Shengli Wang; Yanjun Wang; Zhiyuan He; Chuang Sun; Hugh Sinclair; Yan Chen; Shaowen Liu; Guohui Chen; Fei Xue (Marine and Petroleum Geology, 2023)

Morphological and morphometric analyses of a late Middle Pleistocene hominin mandible from Hualongdong, China - Xiujie Wu; Shuwen Pei; Yanjun Cai; Haowen Tong; Ziliang Zhang; Yi Yan; Song Xing; María Martinón-Torres; José María Bermúdez de Castro; Wu Liu (Journal of Human Evolution, 2023)

Surface-bound sulfate radical-dominated degradation of sulfamethoxazole in the CuFeAl-LDH/peroxymonosulfate system: The abundant hydroxyl groups enhancing efficiency mechanism - Qing Xin; Siqi Liu; Shixu Lu; Zhenyu Chen; Pengzhan Han; Shuaishuai Xin; Qianwen Wang; Guocheng Liu; Chengzhi Zhou; Yanjun Xin; Qinghua Yan (Chemical Engineering Journal, 2023)

Mapping foliar photosynthetic capacity in sub-tropical and tropical forests with UAS-based imaging spectroscopy: Scaling from leaf to canopy - Shuwen Liu; Zhengbing Yan; Zhihui Wang; Shawn Serbin; Marco Visser; Yuan Zeng; Youngryel Ryu; Yanjun Su; Zhengfei Guo; Guangqin Song; Qianhan Wu; He Zhang; et al. (Remote Sensing of Environment, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Cyanide detoxification and iron mineral recycle of cyanide tailings by the sustainable utilization technology of oxidation-reduction roasting: Process optimization and mechanism study - Bing Zhao; Lingbo Zhao; Peng Gao; Yuexin Han; Yanjun Li; Zaizheng Dong; Yan Song (Journal of Environmental Chemical Engineering, 2023)

Enhanced electroenzymatic CO2 reduction by a multifunctional ZIF-8 layer on silica nanoflower with immobilized enzyme - Yaoxuan Li; Lihang Yan; Guanhua Liu; Huaxun Chen; Hao Zhao; Lihui Wang; Jing Gao; Yunting Liu; Xiaobing Zheng; Yanjun Jiang (Chemical Engineering Journal, 2023)

Efficiency and mechanism on photocatalytic degradation of fluoranthene in soil by Z-scheme g-C3N4/α-Fe2O3 photocatalyst under simulated sunlight - Guoliang Yang; Yan Jiang; Bingjie Yin; Guocheng Liu; Dong Ma; Guangshan Zhang; Guodong Zhang; Yanjun Xin; Qinghua Chen (Environmental Science and Pollution Research, 2023)

Benign treatment and resource utilization characteristics of doramectin fermentation residues - Meiqi Pan; Yanjun Xin; Zhilin Wang; Wenqiang Jia; Hongli Lu; Surong Jiang; Zequn Wu; Xiang Chen; Qianwen Wang; Haiyan Du; Qinghua Yan; Guocheng Liu (Journal of Cleaner Production, 2023)

A novel reutilization of ash from biomass gasification process: Feasibility and products improvement analysis - Qianqian Guo; Beibei Yan; Yanjun Hu; Xiang Guo; Wenzhu Wu; Zhanjun Cheng; Guanyi Chen; Li'an Hou (Fuel, 2023)

Rapid determination and health risk assessment of neonicotinoids in source water and tap water of the tropical Hainan Island, China - Zengheng Xiong; Yan Wu; Yang Zhou; Shuhai He; Danyu Huang; Mingshan Zhang; Yanjun Jiang; Long Cheng; Zhendong Zhao; Hongwei Zhao; Huan Lin (Environmental Science and Pollution Research, 2023)

Associations between congenital heart disease and air pollutants at different gestational weeks: a time-series analysis - Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Zhou; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Geochemistry and Health, 2023)

China’s Black Soil Granary is increasingly facing extreme hydrological drought threats - Mengzhu Liu; Ying Guo; Xiaolong Zhang; Yan-Jun Shen; Yucui Zhang; Hongwei Pei; Leilei Min; Shiqin Wang; Yanjun Shen (Science Bulletin, 2023)

Microstructure damage characteristics and its mechanism of undisturbed loess suffering to weak acid leaching - Lei Zhang; Ruixin Yan; Jianbing Peng; Yanjun Shen; Jinyuan Zhang; Yu Zhang (Bulletin of Engineering Geology and the Environment, 2023)

Critical tectonic events and their geological controls on deep buried coalbed methane accumulation in Daning-Jixian Block, eastern Ordos Basin - Taotao Yan; Shan He; Shuai Zheng; Yadong Bai; Wei Chen; Yanjun Meng; Shangwen Jin; Huifang Yao; Xiaobao Jia (Frontiers of Earth Science, 2023)

Constitutive relation and particle size distribution model of rock fragments in the goaf - Qian Liu; Baiquan Lin; Yan Zhou; Yanjun Li (Environmental Science and Pollution Research, 2023)

Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China - Xiaoyu Tian; Xiaobing Shan; Li Ma; Chenyang Zhang; Mei Wang; Jie Zheng; Ruoyi Lei; Li He; Jun Yan; Xun Li; Yanjun Bai; Keqin Hu; et al. (Environmental Pollution, 2023)

Association between air pollutants and neural tube defects during pregnancy in Lanzhou, China: a time series analysis - Yan Yang; Li Zhou; Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Pan; Yanbei Huo; Ruijuan Wang; Yupei Ba; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2023)

Time series analysis on association between ambient air pollutants and orofacial clefts during pregnancy in Lanzhou, China - Yanyan Liu; Li Zhou; Wenling Zhang; Yanjun Yang; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2022)

Effects of inhomogeneity on mechanical properties of granites in Songliao Basin using the grain-based model - Tianrui Yang; Ziwang Yu; Yanjun Zhang; Jianguo Kang; Xiaoqi Ye; Chaohui Yan (Arabian Journal of Geosciences, 2022)

A Single Administration of Riluzole Applied Acutely After Spinal Cord Injury Attenuates Pro-inflammatory Activity and Improves Long-Term Functional Recovery in Rats - Qichao Wu; Wenkai Zhang; Shuo Yuan; Yanjun Zhang; Wenxiu Zhang; Yan Zhang; Xueming Chen; Lei Zang (Journal of Molecular Neuroscience, 2022)

Orexin A peptidergic system: comparative sleep behavior, morphology and population in brains between wild type and Alzheimer’s disease mice - Peng Zhao; Yaqian You; Zhe Wang; Yanjun Zhou; Gaoshang Chai; Gen Yan; Zhewu Jin; Qing Wang; Hongxu Sun (Brain Structure and Function, 2022)
Sleep disturbance is common in patients with Alzheimer’s disease (AD), and orexin A is a pivotal neurotransmitter for bidirectionally regulating the amyloid-β (Aβ) deposition of AD brain and poor sleep. In the present study, we examined the characteristic of sleep–wake architecture in APPswe/PSldE9 (APP/PS1) and Aβ-treated mice using electroencephalogram (EEG) and electromyographic (EMG) analysis. We compared the expression of orexin A, distribution, and morphology of the corresponding orexin A-positive neurons using innovative methods including three-dimensional reconstruction and brain tissue clearing between wild type (WT) and APP/PS1 mice. Results from our study demonstrated that increased wakefulness and reduced NREM sleep were seen in APP/PS1 and Aβ treated mice, while the expression of orexin A was significantly upregulated. Higher density and distribution of orexin A-positive neurons were seen in APP/PS1 mice, with a location of 1.06 mm–2.30 mm away from the anterior fontanelle compared to 1.34 mm–2.18 mm away from the anterior fontanelle in WT mice. These results suggested that the population and distribution of orexin A may play an important role in the progression of AD.

Dysregulated lncRNA and mRNA may promote the progression of ischemic stroke via immune and inflammatory pathways: results from RNA sequencing and bioinformatics analysis - Yingshuang Wang; Feifei Feng; Pingping Zheng; Lijuan Wang; Yanjun Wang; Yaogai Lv; Li Shen; Kexin Li; Tianyu Feng; Yang Chen; Zhigang Liu; Yan Yao (Genes & Genomics, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Identification of hub lncRNA ceRNAs in multiple sclerosis based on ceRNA mechanisms - Yanjun Ding; Taotao Li; Xinwei Yan; Mintian Cui; Chao Wang; Situo Wang; Fengmin Zhang; Ruijie Zhang (Molecular Genetics and Genomics, 2021)

Adsorption Characteristics of Tetracycline onto Biochars as Affected by Solution Chemistry Conditions and Ball Milling Treatment - Xiaohan Ma; Yanjun Xin; Qinghua Yan; Xiangrui Pan; Shuaishuai Xin; Xiaomin Huang; Qinghua Chen; Guocheng Liu (Water, Air, & Soil Pollution, 2020)

Population genetic divergence in Lycium chinense Mill. (Solanaceae) is driven by both hybridization and geo-environmental factors - Lulu Yang; Yan He; Shuhui Wang; Yanjun Zhang; Ying Wang; Qiong Liang (Genetic Resources and Crop Evolution, 2020)

The treatment and follow‐up of ‘recurrence’ with discharged COVID ‐19 patients: data from Guizhou, China - Maolu Tian; Yanjun Long; Yang Hong; Xiangyan Zhang; Yan Zha (Environmental Microbiology, 2020)
Summary We reported 20 cases of discharged COVID‐19 patients whose RT‐PCR test results showed ‘re‐positive’. After finding ‘re‐positive’, these patients were admitted to hospital for the second time and were followed up until the end of May 2020. We recorded detailed treatment and follow‐up process, and collected relevant data. The possible causes and potential clinical significance of this phenomenon are discussed.

Permeability dynamic variation of coal under various confining pressures using LFNMR relaxation method - Peng Xia; Fangui Zeng; Xiaoxia Song; Beilei Sun; Taotao Yan; Wei Li; Yanjun Meng (Arabian Journal of Geosciences, 2020)

Growing‐season temperature and precipitation are independent drivers of global variation in xylem hydraulic conductivity - Pengcheng He; Sean M. Gleason; Ian J. Wright; Ensheng Weng; Hui Liu; Shidan Zhu; Mingzhen Lu; Qi Luo; Ronghua Li; Guilin Wu; Enrong Yan; Yanjun Song; et al. (Global Change Biology, 2020)
Stem xylem‐specific hydraulic conductivity ( K S ) represents the potential for plant water transport normalized by xylem cross section, length, and driving force. Variation in K S has implications for plant transpiration and photosynthesis, growth and survival, and also the geographic distribution of species. Clarifying the global‐scale patterns of K S and its major drivers is needed to achieve a better understanding of how plants adapt to different environmental conditions, particularly under climate change scenarios. Here, we compiled a xylem hydraulics dataset with 1,186 species‐at‐site combinations (975 woody species representing 146 families, from 199 sites worldwide), and investigated how K S varied with climatic variables, plant functional types, and biomes. Growing‐season temperature and growing‐season precipitation drove global variation in K S independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes. This highlights an important role for K S in predicting shifts in community composition in the face of climate change.

Potential sources and associated risk assessment of potentially toxic elements in paddy soils of a combined urban and rural area - Yanjun Chai; Yan Li; Xiaolei Chen; Jin Zhang; Peter Christie; Ka Lai Chow; Chao Ai; Shengdao Shan (Environmental Science and Pollution Research, 2019)

Application of Avaatech X-ray fluorescence core-scanning in Sr/Ca analysis of speleothems - Dong Li; Liangcheng Tan; Fei Guo; Yanjun Cai; Youbin Sun; Gang Xue; Xing Cheng; Hong Yan; Hai Cheng; R. Lawrence Edwards; Yongli Gao; Jessica Kelley (Science China Earth Sciences, 2019)

Transplantation of umbilical cord–derived mesenchymal stem cells on a collagen scaffold improves ovarian function in a premature ovarian failure model of mice - Yanjun Yang; Lei Lei; Shanshan Wang; Xiaoqiang Sheng; Guijun Yan; Lu Xu; Jingyu Liu; Mengyuan Liu; Xin Zhen; Lijun Ding; Haixiang Sun (In Vitro Cellular & Developmental Biology - Animal, 2019)

Rural solid waste—characteristics and leachate pollution assessment for different precipitation levels, China - Huiyuan Yang; Bo Yue; Yanjun Liu; Xiaohui Wu; Hong Gao; Zhibin Zhang; Zhuoyi Yan (Environmental Science and Pollution Research, 2019)

Follicular helper T cell and memory B cell immunity in CHC patients - Yong Liu; Huifan Ji; Pingwei Zhao; Hongqing Yan; Yanjun Cai; Lei Yu; Xiaoli Hu; Xiguang Sun; Yanfang Jiang (Journal of Molecular Medicine, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Clinical evaluation of a panel of multiplex quantitative real-time reverse transcription polymerase chain reaction assays for the detection of 16 respiratory viruses associated with community-acquired pneumonia - Dan Zhang; Haiyan Mao; Xiuyu Lou; Junhang Pan; Hao Yan; Hongfeng Tang; Yan Shu; Yun Zhao; Xiaoli Cheng; Hong Tao; Yanjun Zhang; Xuejun Ma (Archives of Virology, 2018)

Pharmacokinetics and immunogenicity of T0001, a newly developed anti-TNFα fusion protein, in healthy volunteers - Yitong Wang; Chang Liu; Shi Chen; Wei Wang; Lihou Dong; Qian Wang; Yan Wang; Libo Zhao; Yannan Zang; Zhenwei Xie; Yang Liu; Yanjun Liu; et al. (European Journal of Clinical Pharmacology, 2017)

Establishment and Application of a Method for Rapid Determination of Total Sugar Content Based on Colorimetric Microplate - Yonggang Wang; Yanjun Jing; Feifan Leng; Shiwei Wang; Fan Wang; Yan Zhuang; Xiaofeng Liu; Xiaoli Wang; Xueqing Ma (Sugar Tech, 2017)

Characteristics of volatile compound emission and odor pollution from municipal solid waste treating/disposal facilities of a city in Eastern China - Hanwen Guo; Zhenhan Duan; Yan Zhao; Yanjun Liu; Muhammad Farooq Mustafa; Wenjing Lu; Hongtao Wang (Environmental Science and Pollution Research, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Association of single nucleotide polymorphisms of IL23R and IL17 with necrotizing enterocolitis in premature infants - Jiayi Tian; Yanjun Liu; Yanfang Jiang; Haohan Zhou; Tong Zhu; Xiaoqi Zhao; Liping Peng; Chaoying Yan (Molecular and Cellular Biochemistry, 2017)

Two new coumarins from the bark of Streblus indicus (Bur.) Corner - Ruijie He; Shengping Deng; Hui Nie; Yan Huang; Buming Liu; Ruiyun Yang; Shuai Huang; Dexiong Zhou; Huangcan Chen; Jun Li; Yanjun Zhang (Natural Product Research, 2017)

A comparison of atmospheric temperature over China between radiosonde observations and multiple reanalysis datasets - Yanjun Guo; Siqi Zhang; Jinghui Yan; Zhe Chen; Xin Ruan (Journal of Meteorological Research, 2016)

Modifications to the GSI for granite in drilling - Daming Lin; Yan Sun; Wei Zhang; Renmao Yuan; Wantong He; Bo Wang; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2014)

Development of novel AllGlo-probe-based one-step multiplex qRT-PCR assay for rapid identification of avian influenza virus H7N9 - Yanjun Zhang; Haiyan Mao; Juying Yan; Xinying Wang; Lei Zhang; Koch Guus; Hui Li; Zhen Li; Yin Chen; Liming Gong; Zhiping Chen; Shichang Xia (Archives of Virology, 2014)

Geochronologies of the Huaixi copper-gold deposit and the Caomen alkaline granite, SE China: implications for tectonic evolution - Yanjun Li; Junhao Wei; Jun Tan; Chunliang Yao; Lina Peng; Guangling Xiao; Yunfei Yan; Zefu Ye (International Geology Review, 2011)

Trend in pan evaporation and its attribution over the past 50 years in China - Min Liu; Yanjun Shen; Yan Zeng; Changming Liu (Journal of Geographical Sciences, 2010)

Ectopic over-expression of BhHsf1, a heat shock factor from the resurrection plant Boea hygrometrica, leads to increased thermotolerance and retarded growth in transgenic Arabidopsis and tobacco - Yan Zhu; Zhi Wang; Yanjun Jing; Lili Wang; Xia Liu; Yongxiu Liu; Xin Deng (Plant Molecular Biology, 2009)

Cyclophosphamide promotes pulmonary metastasis on mouse lung adenocarcinoma - Shuli Man; Yanjun Zhang; Wenyuan Gao; Lulu Yan; Chaoyi Ma (Clinical & Experimental Metastasis, 2008)